1971
DOI: 10.1016/s0010-2180(71)80085-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of explosion limit chemical kinetics in H2-CO-O2 detonations

Abstract: The role of explosion limit kinetics is explored by applying three different explc, sion limits to detonation waves traveling at a critical Mach number in stoiehiometrie mixture of H:-COO 2. Such waves are achieved by subjecting normal Chapman-Jouguet waves to a gaseous boundary and bringing them to a critical veloeit~t below which quenching would re/mlt. It is found that the critical velocities can be explained by the explos:on limit adv,~nced by Minkoff and Tipper when recent applicable rate constants (sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In fact the velocity of limit detonations can be substantially different from the C-J value and need not be constant even in the same mixture-however, the mean velocity is usually only slightly lower than the C-J value within a few per cent of the limit, as can be seen from measurements quoted by Lewis and von Elbe (1961), and so this assumption should only lead to slightly narrower predicted than measured limits, the discrepancy depending on the definition of a detonation. Further support for this comes from Lu et al (1971) who showed that detonations in stoichiometric CO-H.-O. mixtures failed if the velocity was reduced by more than 10% which is a similar reduction to that predicted by Zeldovich (1940) when considering losses to the tube walls.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In fact the velocity of limit detonations can be substantially different from the C-J value and need not be constant even in the same mixture-however, the mean velocity is usually only slightly lower than the C-J value within a few per cent of the limit, as can be seen from measurements quoted by Lewis and von Elbe (1961), and so this assumption should only lead to slightly narrower predicted than measured limits, the discrepancy depending on the definition of a detonation. Further support for this comes from Lu et al (1971) who showed that detonations in stoichiometric CO-H.-O. mixtures failed if the velocity was reduced by more than 10% which is a similar reduction to that predicted by Zeldovich (1940) when considering losses to the tube walls.…”
Section: Introductionsupporting
confidence: 52%
“…Kinetic data on the explosion limit is not available for most mixtures but Lu et al (1971) have applied the same criteria for H.-CO-O. mixtures to select the best reaction scheme and rates by comparison with the results of Laffitte (1938) and Lewis and von Elbe (1961).…”
Section: Introductionmentioning
confidence: 99%